ANALYSIS OF ANXIETY AS A PSYCHOLOGICAL PHENOMENON AND USING ART THERAPY WORK WITH CLAY IN THERAPY FOR ANXIETY - Podolska, Anna (PSYCHOLOGICAL JOURNAL, 2021)
The article contains an exposition of the theoretical analysis of the main scientific approaches to the study of the concept of "anxiety states" and the differentiation and correlation of the concepts of anxiety, situational and personal anxiety, anxiety state. The psychological, physiological and social aspects of the emergence and manifestation of anxiety states are analyzed. Phobic to asthenic components of anxiety states are described. The reasons and consequences of anxiety in various senses of anxiety as an emotional and psychological state are considered. We see the importance of studying anxiety states in the growth trend of negative emotions in society, and in the demand for psychological support. Among modern methods of psychotherapy for anxiety states, we choose art therapy as one of the ecological means of overcoming feelings of fear, anger, shame and other negative emotional states. Particular attention is paid to the consideration of art therapy work with clay as a psychotherapeutic method of anxious personality states. A description is made and general characteristics and features of art therapy work with clay are given. Based on the study of a number of foreign studies on art therapy with clay, we saw evidence of a close correlation between the physiological and psychological aspects of human life through the experience of contact, as one of the very first basic personal experiences. When interacting with clay in the context of an art therapy process, each hand movement provides instant feedback to the brain, provides non-verbal access to psychological and sensorimotor processes. Natural clay is a natural, ecological and affordable material that provides the creation of three-dimensional objects and naturally promotes significant psychological processes through touch, revealing significant information about the inner world of the creators. Therefore, clay art therapy can be a powerful tool for solving many basic problems and stimulating an individual to social-emotional development. The relevance of the upcoming study is due to the urgent need to use psychotherapeutic methods of an innovative and systemic nature in working with anxiety states. We determine the prospect of our research in the development of a program for a therapeutic program for anxiety states using clay as a method of art therapy.